Putative Loci Causing Early Embryonic Mortality in Duroc Swine - Zhang, Chunyan; MacNeil, Michael D.; Kemp, Robert A.; Dyck, Michael K.; Plastow, Graham S. (Frontiers in Genetics, 2018)
Lethal recessive variants are usually maintained at relatively low frequencies in populations as heterozygous state. However, they can cause prenatal death of homozygous offspring which may result in smaller litter size in pigs. This study aimed to detect the putative lethal variants in the Duroc breed and estimate their harmful effects on five fertility traits: total number of born (TNB), number of born alive (BA), number alive at 24h (L24), stillborn piglets (SB), and number of mummified fetuses (MM). Imputed genotypes of 650K SNPs for 1359 Duroc boars were used in this study. Eight SNPs were detected (P < 0.01) and the most significant one (P = 1.7E-11) was located on SSC14 with 45.3 homozygous individuals expected but none observed. Haplotype analyses detected 152 haplotypes as potentially harboring recessive lethal mutations. Twenty-six of them were confirmed in the association studies as they showed significantly harmful effects on at least one fertility trait. The most important regions were located on SSC8 (Hap14), SSC9 (Hap16), SSC11 (Hap17), SSC12 (Hap18), SSC14 (Hap21) and SSC17 (Hap26) which were significant for the fertility traits in both random and designed matings. A few candidate genes identified within these five regions were described as being involved in spermatogenesis and male fertility (TEX14, SEP4 and HSF5), or displayed recessive lethality (SCD5 and PCF11) in other species. The putative loci detected in this study provide valuable information to potentially increase Duroc litter size by avoiding carrier-by-carrier matings in breeding programs. Further study of the identified candidate genes responsible for such lethal effects may lead to new insights into functions regulating pig fertility.